Proctoscopy should be mandatory in men that have sex with men with external anogenital warts - Mlakar, Boštjan (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
INTRODUCTION: The aim of this study was to evaluate anal pathology in men having sex with men (MSM) seen at our proctology outpatient clinics. METHODS: The charts of 74 MSM treated by the author between January 2002 and April 2006were reviewed. RESULTS: Three of 74 patients (4%) had proctitis and 96% had anogenital condylomata acuminata (warts). 49 out of 71 (69%) had external anogenital as well as intra-anal warts and 13 (18%) had only intra-anal warts.In 14 an intra-anal dysplasia and in 2 patients intra-anal verrucous carcinomas were detected. The average duration of disease before referral to our institutions was more than 9 months. Half of the patients were previously treated for anogenital warts with ointments and suppositories at other institutions, including 17 that were "treated" with ointments and/or suppositories for hemorrhoids prescribed by family physicians. The patients mostly had widespread disease and sixty-nine of them required surgery. In the follow-up period there was no recurrence of warts and only itching was observed in 31 (44%) patients. Therapy with imiquimod was introduced for 3 months in twenty-two cases with intra-anal dysplasia. No major side effects were noticed despite intra-anal use. CONCLUSION: Proctoscopy and histological examination of intra-anal lesions in cases of external anogenital warts shouldbe mandatory in MSM patients. I would like to encourage other physiciansto use this approach, which enables detection of intra-anal warts, dysplasia, and even carcinoma in the asymptomatic stage.
Keywords: Adult; Cohort Studies; Complications; Condylomata Acuminata; Dejavniki tveganja; Diagnosis; Epidemiology; Homoseksualnost moških; Homosexuality, Male; Incidenca; Incidence; Kohortne študije; Kondilomata akuminata; Odrasli; Pathology; Ponovitev; Proctitis; Proctoscopy; Proktitis; Proktoskopija; Psychology; Recurrence; Retrospective Studies; Retrospektivne študije; Risk Factors; Therapy